2003
DOI: 10.1007/s00248-002-1012-5
|View full text |Cite
|
Sign up to set email alerts
|

Buoyancy Regulation and the Potential for Vertical Migration in the Oceanic Cyanobacterium Trichodesmium

Abstract: Diel protein and carbohydrate content in Trichodesmium thiebautii was measured to evaluate the relationship to buoyancy status. Carbohydrate:protein ratio was the best predictor of buoyancy and fit a cosine curve with increasing values during the day and decreasing values at night in cycles that paralleled observed diel buoyancy patterns. This ratio also increased in short-term experiments as a function of light and increased in parallel with decreasing positive buoyancy. We used changes in this ratio to estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(126 citation statements)
references
References 34 publications
5
120
0
1
Order By: Relevance
“…Although artificially expedited using dense batch cultures (Figure 1), bloom formation in our water column possessed notable similarities to natural blooms observed in tropical oceans, where surface slicks of dense Trichodesmium aggregations develop under calm conditions with sea surface temperatures of ± 26 1C, high solar irradiance and high concentrations of Fe and P (Karl et al, 2002;Le Borgne, 2008, 2010;Bergman et al, 2012). In these oceanic blooms, the vertical ascent of Trichodesmium cells due to positive buoyancy (Villareal and Carpenter, 2003;Le Borgne, 2008, 2010) occurs simultaneously with rapid growth rates, both processes accounting for the hastened, ultra-dense accumulation of cells at the surface Le Borgne, 2008, 2010;Bergman et al, 2012).…”
Section: Formation Of Trichodesmium Surface Bloomsupporting
confidence: 54%
“…Although artificially expedited using dense batch cultures (Figure 1), bloom formation in our water column possessed notable similarities to natural blooms observed in tropical oceans, where surface slicks of dense Trichodesmium aggregations develop under calm conditions with sea surface temperatures of ± 26 1C, high solar irradiance and high concentrations of Fe and P (Karl et al, 2002;Le Borgne, 2008, 2010;Bergman et al, 2012). In these oceanic blooms, the vertical ascent of Trichodesmium cells due to positive buoyancy (Villareal and Carpenter, 2003;Le Borgne, 2008, 2010) occurs simultaneously with rapid growth rates, both processes accounting for the hastened, ultra-dense accumulation of cells at the surface Le Borgne, 2008, 2010;Bergman et al, 2012).…”
Section: Formation Of Trichodesmium Surface Bloomsupporting
confidence: 54%
“…It has been hypothesized that this organism may migrate to the phosphocline, store P as polyP, and return to the surface in a process termed P-mining (Karl et al 1992;Villareal and Carpenter 2003). Although this could result in elevated polyP, the phosphocline ranged from 160 to 300 m on this transect, which is deeper than Trichodesmium is likely to migrate (White et al 2006a), and is deeper than Trichodesmium is typically observed in this region (Orcutt et al 2001;Davis and McGillicuddy 2006).…”
Section: Discussionmentioning
confidence: 82%
“…Two of the most abundant transcripts in the low-salinity offshore, transitional and oceanic Trichodesmium transcriptomes were from gas vesicle protein genes adjacent to each other in the genome. Gas vesicles provide buoyancy to return to surface waters after Trichodesmium sinks to depth, possibly to acquire phosphorus (Villareal and Carpenter, 2003). Gas vesicles are important for remaining in the photic zone.…”
Section: Discussionmentioning
confidence: 99%